Implementing fluorescent MOFs as down-converting layers in hybrid light-emitting diodes. Issue 8 (7th February 2019) - Angioni, Enrico; Marshall, Ross J.; Findlay, Neil J.; Bruckbauer, Jochen; Breig, Benjamin; Wallis, David J.; Martin, Robert W.; Forgan, Ross S.; Skabara, Peter J.
Abstract : Anchoring a down-converting chromophore to a MOF scaffold enhances the efficiency of the resulting hybrid LED by negating aggregation-induced quenching. Abstract : One of the most important non-radiative relaxation processes that limits the quantum yield of a fluorophore is related to aggregation of the molecules in the solid-state causing excimer quenching. To limit this quenching mechanism, the fluorophore can be contained within a well-ordered 3D system that minimises aggregation through rigid bonds and spatial separation in a defined topological construct. Herein, the synthesis, characterisation and application as a down-converter of a new luminescent 3D material (MOF-BTBMBA ) that incorporates a building block based on a benzothiadiazole (BT) derivative (BTBMBA ) in a metal–organic framework (MOF) is presented. Notably, the photoluminescence quantum yield and hybrid LED performance are significantly improved for the MOF-based device compared to that prepared with the free ligand, highlighting the effectiveness of the rigid scaffold arrangement.